The NICT in training research from virtuality case study of research and innovation E-InnovaCMM Metalmechanical Center - Cárdenas Espinosa, Rubén Darío
This article presents the case of the virtual E-InnovaCMM research and innovation seedbed of the SENA Capital District Metlamecánico Center, as a training strategy in formative research in context, in which BLearning is applied through the PACIE Model (Presence, Scope, Training, Interaction and Elearning) directed from the Subdirectorate and the Research Group GICEMET options to carry out research from the Titula formation programs in virtual or distance modality, or from options to carry out the practical stage through the support of the Center's projects.